Effects of high-intensity resistance training on bone mineral density in young male powerlifters - Tsuzuku, S.; Ikegami, Y.; Yabe, K. (Calcified Tissue International, 1998)
The effects of high-intensity resistance training on bone mineral density (BMD) and its relationship to strength were investigated. Lumbar spine (L2-L4), proximal femur, and whole body BMD were measured in 10 male powerlifters and 11 controls using dual-energy X-ray absorptiometry (DXA). There were significant differences in lumbar spine and whole body BMD between powerlifters and controls, but not in proximal femur BMD. A significant correlation was found between lumbar spine BMD and powerlifting performance. These results suggest that high-intensity resistance training is effective in increasing the lumbar spine and whole body BMD.